Normative Values for Heart Rate Variability Parameters in School-Aged Children: Simple Approach Considering Differences in Average Heart Rate - Gąsior, Jakub S.; Sacha, Jerzy; Pawłowski, Mariusz; Zieliński, Jakub; Jeleń, Piotr J.; Tomik, Agnieszka; Książczyk, Tomasz M.; Werner, Bożena; Dąbrowski, Marek J. (Frontiers in Physiology, 2018)
Background: Heart rate variability (HRV) analysis is a clinical tool frequently used to characterize cardiac autonomic status. The aim of this study was to establish normative values for short-term HRV parameters by considering their main determinants in school-aged children. Methods: Five-minute electrocardiograms were taken from 312 non-athlete children (153 boys) at age of 6 to 13 years for computation of conventional time- and frequency-domain HRV parameters. Heart rate (HR), respiratory rate, age, body mass index and sex were considered as their potential determinants. Multiple regression analysis revealed that HR was the principal predictor of all standard HRV indices. To develop their universal normative limits, standard HRV parameters were corrected for prevailing HR. Results: The HRV correction for HR yielded the parameters which became independent on both sex and HR, and only poorly dependent on age (with small effect size). Normal ranges were calculated for both time- and frequency domain indices (the latter computed with either fast Fourier transform and autoregressive method). To facilitate recalculation of standard HRV parameters into corrected ones, a calculator was created and attached as a supplementary material that can be downloaded and used for both research and clinical purposes. Conclusions: This study provides HRV normative values for school-aged children which have been developed independently of their major determinants. The calculator accessible in the supplementary material can considerably simplify determination if HRV parameters accommodate within normal limits.